2011
DOI: 10.1177/0883073810381279
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Resonance Spectroscopy in the Diagnostic Evaluation of Brainstem Lesions in Alexander Disease

Abstract: Alexander disease is a progressive neurodegenerative disease, which can present with brainstem lesions with imaging characteristics similar to multifocal low-grade glioma, thus presenting a diagnostic dilemma. The authors report a 6-year-old child presenting with multifocal brainstem lesions subsequently diagnosed to have Alexander disease. In vivo magnetic resonance spectroscopy generated a metabolite profile of the lesion allowing differentiation from low-grade glioma. Magnetic resonance spectroscopy is a po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 20 publications
1
7
0
Order By: Relevance
“… 5 , 18 , 19 Additional information provided by magnetic resonance spectroscopy, another non‐invasive tool, can also help in discriminating brainstem lesions. 20 , 21 , 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 5 , 18 , 19 Additional information provided by magnetic resonance spectroscopy, another non‐invasive tool, can also help in discriminating brainstem lesions. 20 , 21 , 22 , 23 …”
Section: Discussionmentioning
confidence: 99%
“…5,18,19 Additional information provided by magnetic resonance spectroscopy, another non-invasive tool, can also help in discriminating brainstem lesions. [20][21][22][23] However, other studies argue that diagnosis of brainstem lesions made by radiological examination alone is unreliable. Rachinger et al reported that the specificity of MRI was 46.6% and sensitivity was 62.5% in patients with low grade gliomas (WHO grades I and II), and the specificity was 61.7% and sensitivity was 58.3% in patients with high-grade gliomas (WHO grades III and IV).…”
Section: Discordance Between Radiological Diagnosis and Pathological Diagnosismentioning
confidence: 99%
“…MRI techniques have significantly advanced in recent years with new imaging techniques being able to provide information on tissue properties, structure, and basic metabolic processes. Amongst these new techniques, 1 H-MR spectroscopy (MRS) has the ability to provide non-invasive measurements of metabolite profiles with the potential to aid diagnosis and improve the characterization of pediatric brain tumors (3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…They comprise approximately 25% of all pediatric cancers and are the leading cause of cancer death in children (1). 1 H-magnetic resonance spectroscopy (MRS) has been used as a noninvasive diagnostic tool for a variety of pathologies (2)(3)(4) and there are number of studies on the significant contribution of MRS for the characterization of pediatric brain tumors (5)(6)(7)(8)(9). Pattern recognition based classification of brain tumors using MRS data has been investigated thoroughly for more than two decades now (6,8,10,11) and its application for discriminating childhood brain tumors has been explored in single and multicenter studies.…”
Section: Introductionmentioning
confidence: 99%